Rancang Bangun Sistem Informasi E-Learning Berbasis Website di SMA Negeri 1 Majalaya - Nugraha, Muhamad Fahmi; Sandika, Andy Muhammad; Tryana, Anjas (Ma'soem University, 2025)
SMA Negeri 1 Majalaya is a senior high school located on Jalan Panyadap Majalaya No. 2 Kec. Solokanjeruk Kab. Bandung. Teaching and learning activities carried out by the school mostly still use conventional methods, namely face-to-face where the teacher enters the class to take attendance, deliver material and give assignments. In practice, there are concerns felt by the school, such as the vulnerability of attendance data, materials and the slow process of evaluating or assessing student performance. The method used in the development of information systems in this study is Rapid Application Development which emphasizes a relatively short development cycle with a system development cycle including Requirement, Design, Implement, Test, and Maintenance. The design of this e-learning information system is expected to be a solution in overcoming the vulnerability of attendance data and materials that can be lost or damaged. Then the e-learning information system can help teachers in evaluating or assessing student performance quickly and easily with the print or export feature on student grade reports. The expected alternative learning media has also been completed and can be used properly in achieving the previously set goals.